Efektivitas Kolam Retensi dalam Penanganan Bencana Banjir di Kecamatan Jatinangor, Kabupaten Sumedang - Luthfiya A'yuni; Hilwati Hindersah (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Flood disaster is one of the disasters that often occur in Jatinangor District. Floods in the Jatinangor District have an impact on residential and agricultural areas. The government implemented the construction of a retention pond as a flood control effort in the Jatinangor District. This study aims to identify the optimization of the application of retention ponds in handling floods in the Jatinangor District. The main cause of the flood disaster in Jatinangor District is the narrowing of the Cikeruh River due to the deposition of mud and garbage. Retention ponds are able to handle planned inundation worth 4.08% at the administrative scope, 4.09% at the sub-watershed scope, and 295% at the scope of the area directly affected by the presence of retention ponds or areas within a 400 meter radius of the retention pond location. The retention pond effectively overcame inundation in the neighboring areas, so that the retention pond could evacuate the residential area consisting of 948 houses from flooding. The retention pond did not effectively alleviate flooding at the administrative and sub-watershed levels. Abstrak. Bencana banjir merupakan salah satu bencana yang cukup sering terjadi di Kecamatan Jatinangor. Banjir di Kecamatan Jatinangor berdampak pada kawasan permukiman dan pertanian. Pemerintah menerapkan pembangunan kolam retensi sebagai Upaya pengendalian banjir di Kecamatan Jatinangor. Tujuan dari penelitian ini yaitu untuk mengidentifikasi optimalisasi penerapan kolam retensi dalam penanganan banjir di Kecamatan Jatinangor. Penyebab utama bencana banjir di Kecamatan Jatinangor yaitu penyempitan Sungai Cikeruh akibat pengendapan lumpur dan sampah. Kolam retensi mampu menangani genangan rencana senilai 4,08% pada lingkup administrasi, 4,09% pada lingkup sub-DAS, dan 295% pada lingkup wilayah yang secara langsung terdampak oleh keberadaan kolam retensi atau wilayah dalam radius 400 meter dari lokasi kolam retensi. Kolam retensi secara efektif mengatasi genangan pada wilayah di dekatnya, sehingga keberadaan kolam retensi dapat mengevakuasi kawasan permukiman yang terdiri dari 948 rumah di sekitarnya dari bencana banjir. Kolam retensi tidak mengatasi banjir secara efektif pada lingkup administrasi dan sub-DAS.